Non-specific risk factors of early period of primary tuberculosis infection in children - Sukhanova, Lidia; Bilogortseva , Olga; Zosimov, Anatolyi; Gerasimova, Tatiana; Volianskyi, Andrii; Smilyanskaya, Maya; Didorenko, Tatiana (Annals of Mechnikov's Institute, 2023)
The influence of numerous non-specific factors has not been sufficiently studied. The lack of works in which the influence of a whole complex of factors was determined on the same group was the basis for this study. Study the features and values of the spectrum of nonspecific risk factors for the early period of primary tuberculosis (EPPT) in the children at the present stage. Risk factors for the occurrence of EPPT in children can be conditionally divided into specific and non-specific. Factors characterizing the specifics of tuberculosis contact and BCG vaccination are classified as specific. All other factors that are related to the impact on the resistance of the child's body are considered non-specific. Today, specific risk factors are well studied. Specialists have no doubt about the negative impact of tube contact and the absence or inefficient BCG vaccination or revaccination. In relation to non-specific risk factors, the role of microsocial factors has been determined to a greater extent: material standard of living, sanitary literacy and culture, housing conditions. The effect of radionuclide contamination of residential areas on the course of tuberculosis in children was also revealed. Among the risk factors for the emergence EPPT the whole is involved a member of nonspecific factors such as genetic cargo on the part of the parents, the disappointing course of pregnancy and childbirth, transferred childhood infections, and the presence of a child with a concomitant pathologic and unpleasant microsocial state. The beginning of the formation of risk factors EPPT falls for the period before the leading the child (genetic cargo). Then in time measurement to him join perinatal factors, transferred childhood infections, concomitant pathology and microsocial factors. The highest predictive significance revealed: complicated childbirth, mass birth of baby at birth, Living space and educational level of the mother.